2024
DOI: 10.1039/d3ta05975h
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the synergistic effect between the Schottky barrier and field redistribution to achieve high-density, low-consumption, cellulose-based flexible dielectric films for next-generation green energy storage capacitors

Zixiong Sun,
Hansong Wei,
Shibo Zhao
et al.

Abstract: Due to the synergistic effect of field redistribution and the Fermi level's moving, an ESD of 31.07 J cm−3 with η of 80.03% was obtained in the SZS, which is the best performance in cellulose-based dielectric capacitors to the authors' knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 86 publications
(123 reference statements)
0
1
0
Order By: Relevance
“…In addition to the above reasons, compared to the other components, (1 − x )KNN– x BCZT ceramics with x = 0.3 show two-phase coexistence, meaning that the interface area between the T-phase and O-phase also helps to increase its voltage endurance, which has already been proven by lots of studies. 69–71 Due to these two factors, 0.7KNN–0.3BCZT possesses the highest E b of 604.07 kV cm −1 . To confirm such discussions above, the UV-vis absorption spectra of (1 − x )KNN– x BCZT ceramics with x = 0.1, 0.3, and 0.5 are adopted, and the result is plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above reasons, compared to the other components, (1 − x )KNN– x BCZT ceramics with x = 0.3 show two-phase coexistence, meaning that the interface area between the T-phase and O-phase also helps to increase its voltage endurance, which has already been proven by lots of studies. 69–71 Due to these two factors, 0.7KNN–0.3BCZT possesses the highest E b of 604.07 kV cm −1 . To confirm such discussions above, the UV-vis absorption spectra of (1 − x )KNN– x BCZT ceramics with x = 0.1, 0.3, and 0.5 are adopted, and the result is plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Despite their faster charge–discharge speed over the other three most commonly used battery systems, which are Li-ion batteries, fuel cells, and super-capacitors, energy storage capacitors have been suffering from the drawback of short battery life for quite a long time, 1–6 and their development was thus limited. Such a problem is mainly due to the paradox of obtaining large polarization and high electric breakdown strength simultaneously, which have already been reported in many previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the energy storage field, the energy storage density (ESD) of cellulose-based dielectric films has been increased from 5.7 J cm −3 to 27.3 J cm −3 via morphological control, interface modification, and so on. 7–13 As to the field of energy conversation or harvesting, numerous studies on piezoelectric nanogenerators (PENGs) have been reported due to their vast application prospects. Using the in situ synthesis method, micro-flower-like vanadium-doped ZnO was uniformly dispersed in a bacterial cellulose matrix, and a power density ( P D ) of 0.06 μW cm −2 was achieved.…”
mentioning
confidence: 99%
“…The fast charge–discharge capability of dielectric capacitors offers significant advantages over other power systems, with research primarily focusing on enhancing energy storage density ( W rec ) by improving voltage endurance, as detailed in the Supporting Information. However, with the ongoing trend toward the miniaturization of electronics, high W rec is not always essential. Furthermore, indiscriminately increasing the electric breakdown strength ( E b ) of dielectrics leads to a reduction in W rec per unit electric field (WTUEF), a novel concept introduced by the authors to describe the energy efficiency of dielectric capacitors in terms of energy storage per unit breakdown strength ( W rec / E b ).…”
mentioning
confidence: 99%